PENGARUH PELAKSANAAN PROGRAM PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR BALAI PENELITIAN TERNAK (BALITNAK) CIAWI-BOGOR - Recika Recika; Erni Yuningsih (Fakultas Ekonomi Universitas Djuanda, 2017)
This research is descrptive and verification which aims to determinee the effectoof the implementation of education and training programs to work performance of emplooyes at Balitnak Ciawi, Bogor. Population in this research were 30 employes who had attended training and education. Data was collected by questionnaires. All variables in this ressearch is valid and reliable, and feasible to use explain the work performance variable. Results of research conducted shows that eduucation and training simultaneously and partially positive and significant impact on the performance of employees Balitnak. Education variable training has an average score of responses at 4.17, which means both categories, and work performance variable have an average score of responses at 4.32, whicch mean excellent category. it is clear that educatiom and trainiing have a close relationship with job performace.Keyword: education and training programs, work performance of employes.